(untitled) (Baghdad Science Journal, 2023)
Consider a simple graph on vertices and edges together with a total labeling . Then ρ is called total edge irregular labeling if there exists a one-to-one correspondence, say defined by for all where Also, the value is said to be the edge weight of . The total edge irregularity strength of the graph G is indicated by and is the least for which G admits edge irregular h-labeling. In this article, for some common graph families are examined. In addition, an open problem is solved affirmatively.